Psychometric analysis of a tool to assess metamotivational strategies in undergraduate anesthesia students - Ali Norouzi; Mohammad Hossein Shakeri Goki; Fatemeh Atoof; Nazdar Ezzaddin Alkhateeb; Fakhrosadat Mirhosseini (Zanjan University of Medical Sciences and Health Services, 2024)
Background & Objective: Undergraduate anesthesia students benefit from motivational self-regulation strategies when facing specific academic challenges to maintain and improve their academic motivation. Due to the absence of valid and reliable instruments to assess these strategies, the present study aimed at the psychometrical analysis of MSMQ (Metamotivational Strategies in Medical Students) which is used to measure meta-motivational strategies in undergraduate anesthesia students. Materials & Methods: In this psychometric study, 358 undergraduate anesthesia students were selected by convenience sampling method. The research community included undergraduate anesthesia students in Iran, and the MSMQ questionnaire was provided for them to complete. Its validity was determined by face and content validity methods, and its reliability was determined by the internal consistency method. The confirmatory factor analysis method was used to check construct validity. Results: The CVI and CVR values were obtained at ≥ 0.80 for all items. In the confirmatory factor analysis, the factor loading of all items was reported to be ≤ 0.40, and the mentioned instrument enjoyed the goodness of fit indices (RMSEA = 0.064, NNFI = 0.96, CFI = 0.97, SRMR = 0.06, GFI = 0.86). Acceptable reliability coefficients were obtained for the subscales, and Cronbach's alpha coefficient for the whole questionnaire was 0.922. Conclusion: As evidenced by the results of this study, the MSMQ questionnaire is a valid and reliable instrument; therefore, it can be used for Iranian undergraduate anesthesia students.